Are sensory attributes and acceptance influenced by nutritional and health claims of low-sodium salami? Preliminary study with Brazilian consumers - de Almeida, MA (2017)
The authors are grateful to the ‘‘Fundação de Amparo à Pesquisa do Estado de São Paulo" (FAPESP, Brazil) for funding the project nº 2012/07113-2, ‘‘Coordenação de Aperfeiçoamento de Pessoal de Nível Superior" (CAPES) for the M.A. de Almeida Ph.Dscholarshipand Cienciactiva for the E. Saldaña Ph.D Scholarship (Contract 104-2016-FONDECYT) from the ‘‘Consejo Nacional de Ciencia, Tecnología e Innovación Tecnológica" (CONCYTEC, Peru).